Power generation by waves prodcution of a wave generator - Teng, Chris Zhi Tian (2014)
This report presents the detailed process of producing and testing a wave generator. The wave generator is built in the laboratory to simulate the wave environment in the sea. In conjunction with another student’s project, this wave generator will be part of the ‘ocean wave energy to electricity’ harnessing machine.